USING AUTHENTIC MATERIAL TO IMPROVE STUDENTS’ READING INTEREST (A Classroom Action Research in the Second Semester Students of STKIP Siliwangi Bandung) - Aseptiana Parmawati; Rasi Yugafiati (STKIP Siliwangi, 2017)
Reading is a complex process that involves generation and getting information, analyzingmeaning, and making any decision about content.To improve the students’ learning interesttoward reading skill, the lecturer need to know how to teach reading effectively, and whatinstructional materials is the most suitable for their students. Output required of this research asa scientific publication in local journal that have ISSN. The researchers identify some problems,such as: 1) Doesteaching reading using Authentic Material improve the students’ readinginterest?, 2) How is the teaching and learning situation when Authentic Material implemented inthe reading class?. From the result of pre-test, we found that the result of students’ reading wasunder average and still far from what was expected.The finding was supported by the result ofstudents’ reading scores. The average score of pre test was 60.57. After the implementation ofAuthentic Material in every cycle, the students’ reading score were getting better. It can be seenfrom the result of students’ average score Cycle 1 was 64.00 and Cycle 2 was 80.87. It can beconcluded that Authentic Material can improve students’ reading interest and AuthenticMaterial can improve reading classroom into a better situation. Keywords: Authentic Material, Reading Interest, CAR